Cost-effectiveness analysis of colorectal cancer screening strategies in singapore: A dynamic decision analytic approach - Wong S. (Institutional Knowledge at Singapore Management University, 2004)
A dynamic decision analytic framework using local statistics and expert's opinions is put to study the cost-effectiveness of colorectal cancer screening strategies in Singapore. It is demonstrated that any of the screening strategies, if implemented, would increase the life expectancy of the population of 50 to 70 years old. The model also determined the normal life expectancy of this population to be 76.32 years. Overall, Guaiac Fecal Occult Blood Test (FOBT) is most cost effective at SGD162.11 per life year saved per person. Our approach allowed us to model problem parameters that change over time and study the utility measures like cost and life expectancy for specific age within the range of 50-69 through to 70 years old.